2014
DOI: 10.1007/s12024-014-9619-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating infant core temperature response in a hot car using a heat balance model

Abstract: Infants left in vehicles during the workday can reach hazardous thermal thresholds quickly even with mild environmental temperatures. These results provide a seasonal analogue of infant heat stroke time course. Further effort is required to create a universally available forensic tool to predict vehicular hyperthermia time course to demise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The results show that these effects can be expected in less than 30 min. The combination of our dynamic model to calculate the cabin air temperature with a model that describes the man-environment heat exchange would be an appropriate forensic tool to predict hyperthermia time course, as posed by Grundstein et al (2015b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that these effects can be expected in less than 30 min. The combination of our dynamic model to calculate the cabin air temperature with a model that describes the man-environment heat exchange would be an appropriate forensic tool to predict hyperthermia time course, as posed by Grundstein et al (2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The harsh environment inside parked vehicles can cause heat stroke as a life-threatening syndrome observed in human and animals. It may result from exposure to environmental heat stress and is characterised by body core temperatures of >40°C in a human (Grundstein et al 2015a;Grundstein et al 2015b) and >41°C in dogs, as well as by central nervous system dysfunction (Bruchim et al 2009). Not only is the heat stress relevant but also the duration of exposure (Shapiro et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Marty et al [37] found a temperature difference even close to 60 K. As a rough estimation, they assessed the inside temperature due to solar radiation could reach 30 °C for winter time, 60 °C for spring and autumn and up to 90 °C during summer time. The harsh environment inside parked vehicles can cause heat stroke as a life-threatening syndrome observed in human and animals [38, 39] which is documented in the US, by 37 lethal heat stokes by children per year (1998–2015) [33, 40]. …”
Section: Discussionmentioning
confidence: 99%
“…Uncompensable heat stress (UCHS) occurs when evaporative cooling is not supported by the environment, with other conditions (e.g., air temperature levels) impeding cooling [ 58 ]. Although studies have used a T c of 37°C as a level of UCHS [ 27 , 28 ], it is difficult to apply one value to estimate UCHS. This approximation becomes more complex when considering children, as very little empirical core temperature data under heat strain exist.…”
Section: Methodsmentioning
confidence: 99%
“…The avenues and magnitudes of heat loss (evaporative, radiant, convective, and/or conductive exchanges) depend on the environment as well as human physiology/behavior, and are part of an intricate thermoregulatory feedback in the human body [ 38 ]. Thermal balance models can help estimate heat stress and strain in an enclosed space, whether environmentally- or forensically-based [ 3 , 27 ], and further extend the modeled data for more effective communication to parents and caregivers.…”
Section: Introductionmentioning
confidence: 99%